NEW VARIETIES OF PLANTS AND LEGAL PROTECTION OF BREEDERS RIGHT – THE UPOV CONVENTION AND ITS MAJOR ECONOMIC CONSEQUENCES - Ćemalović, Uroš; Petrović, Milica (Economics of Agriculture, 2019)
The International Convention for the Protection of New Varieties of Plants (UPOV Convention) represents the most comprehensive international legal mechanism in this field. In spite of the fact that the UPOV Convention introduces only certain minimal common rules regarding the so called breeders right, the efficiency and the level of acceptance of the entire UPOV system have had numerous economic and social benefits: significant increase of productivity, transparent and just mechanism for rewarding scientific effort and investment in research, important incentive for international trade of new varieties of plants and undisputed impact on agricultural and horticultural development. This paper provides a targeted analysis of the important provisions of the UPOV convention (notion of breeder, grant of breeders right and its content) and examines some of its major economic consequences. It argues that the UPOV convention remains an effective international legal mechanism for the protection of new varieties of plants.